Analisis Puisi “Tapi” Karya Sutardji Calzoum Bachri Dengan Menggunakan Pendekatan Struktural (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Basically, literary works are works that are written in beautiful and orderly language. According to Taum (1997) literature is a form of creation or fiction that is imaginative and uses beautiful language and its presence can be used for other things. One example of a form of literary work is poetry. Poetry is a literary work of high value. Poetry is a literary work that is created as an expression of the wishes, circumstances, and feelings of the author as outlined in poetry (Putu Sudarma 2019). This study discusses the study of a literary work of poetry entitled